Serratia marcescens Peritonitis in a Diabetic Patient Receiving Continuous Ambulatory Peritoneal Dialysis - Kang, Ji Hyoun (The Korean Society of Infectious Diseases and Korean Society for Chemotherapy, 2013)
We report a case of Serratia marcescens peritonitis in a 45-year-old man with insulin-dependent diabetes mellitus undergoing continuous ambulatory peritoneal dialysis (CAPD). The patient presented with abdominal pain and cloudy dialysate. Empiric antibiotic therapy was initiated intraperitoneally with cefazolin and ceftazidime for 5 days. Cultures of the dialysate revealed S. marcescens, and the treatment was subsequently changed to gentamicin and ceftazidime. Oral ciprofloxacin was also added. The patient's abdominal pain and the dialysate white blood cell (WBC) count, however, did not improve. The indwelling CAPD catheter was therefore removed. This is an unusual case report in the Korean literature of S. marcescens peritonitis in a patient receiving CAPD.